2020
DOI: 10.2478/raon-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy

Abstract: BackgroundHigh-risk pulmonary embolism is associated with a high early mortality rate. We report our experience with percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy.Patients and methodsThis was a retrospective analysis of consecutive patients with high-risk pulmonary embolism and contraindications to thrombolytic therapy. They were treated with percutaneous mechanical thrombectomy which included thrombectomy and additional thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…19 Although studies with smaller sample sizes have described overall outcomes of percutaneous pulmonary artery thrombectomy, data focusing on sex disparities do not exist. 6,[20][21][22][23][24][25][26][27][28] In a singlecenter study of 14 patients, in-hospital mortality of 14% was reported, similar to that seen in our study. 27 A multicenter analysis of the Pulmonary Embolism…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…19 Although studies with smaller sample sizes have described overall outcomes of percutaneous pulmonary artery thrombectomy, data focusing on sex disparities do not exist. 6,[20][21][22][23][24][25][26][27][28] In a singlecenter study of 14 patients, in-hospital mortality of 14% was reported, similar to that seen in our study. 27 A multicenter analysis of the Pulmonary Embolism…”
Section: Discussionsupporting
confidence: 90%
“…In another review of patients undergoing thrombectomy, a clinical success rate of 81% to 95% was reported. 22 Bunc et al 28 approximately 32% among a small sample of 25 patients who were treated at a single center with percutaneous pulmonary artery thrombectomy. In a more contemporary retrospective analysis of 34 patients undergoing aspiration thrombectomy, in-hospital mortality of 3% was reported, with even lower complication rates reported in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-based mechanical clot disruption may be an excellent alternative therapeutic method to pharmacologic thrombolysis in cases where thrombolytic therapy is contraindicated, such as patients with recent surgery or such potentially bleeding conditions, or ineffective (60)(61)(62). The pharmacologic dissolution of thrombus to fragments using low dose r-tPA and dislodging the occlusive clot with catheter manipulation and/or balloon angioplasty could be applied in situ for declotting the life-threatening thrombotic shunt.…”
Section: Other Treatments Of Shunt Stenosis or Occlusion And Their Ch...mentioning
confidence: 99%
“…Individual case reports have described the utility of VA‐ECMO and LBT in high‐risk PE patients 8,9 . To our knowledge, this is the first case series describing the use of VA‐ECMO and LBT in the intermediate‐high‐ and high‐risk PE patients 10 . In this report, we describe the presentation, management, and outcomes of a consecutive series of PE patients with hemodynamic compromise requiring VA‐ECMO and LBT.…”
Section: Introductionmentioning
confidence: 95%
“…8,9 To our knowledge, this is the first case series describing the use of VA-ECMO and LBT in the intermediate-high-and high-risk PE patients. 10 In this report, we describe the presentation, management, and outcomes of a consecutive series of PE patients with hemodynamic compromise requiring VA-ECMO and LBT. We selected all patients with PERT activation who required VA-ECMO and LBT within 24 hours of PERT activation.…”
mentioning
confidence: 99%